Skeletal muscle weakness in patients with sarcoidosis and its relationship with exercise intolerance and reduced health status. Issue 1 (23rd December 2004) - Spruit, M A; Thomeer, M J; Gosselink, R; Troosters, T; Kasran, A; Debrock, A J T; Demedts, M G; Decramer, M
Abstract : Background: Skeletal muscle weakness is assumed to be present in patients with sarcoidosis but has never been reported in a consecutive group of patients. Moreover, its relationship with previously observed exercise intolerance and reduced health status has never been studied in these patients. Methods: Pulmonary function, skeletal and respiratory muscle forces, peak and functional exercise capacity, health status, and the circulating levels of inflammatory and anabolic markers were determined in 25 patients with sarcoidosis who complained of fatigue (15 men) and in 21 healthy subjects (13 men). Results: Patients with sarcoidosis had lower respiratory and skeletal muscle forces, reduced exercise capacity and health status, higher anxiety and depression scores, and higher circulating levels of tumour necrosis factor-α than healthy subjects (all p⩽0.01). Its soluble receptor p75 tended to be higher (p = 0.04). Circulating levels of interleukin (IL)-6, IL-8, insulin-like growth factor I and its binding protein 3 were not significantly different between the two groups. Skeletal muscle weakness was related to exercise intolerance, depression, and reduced health status in patients with sarcoidosis, irrespective of age, sex, body weight and height (p⩽0.05). Quadriceps peak torque was inversely related to fatigue but not to the circulating levels of inflammatory or anabolic markers. The mean daily dose of corticosteroids received in the 6 month period before testing was related to quadriceps peak torque only in patients who received oral corticosteroids. Conclusion: Skeletal muscle weakness occurs in patients with sarcoidosis who complain of fatigue and is associated with reduced health status and exercise intolerance.